Organization Income Performance, ZIS Fundrising: Collaboration Brand Network Configuration between Lazismu & Muhammadiyah Enterprises - Savitri, Fania; Suryorini, Ariana; Liddiana, Azzah; Hartono, Setyo (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2026)
Inter-organizational networks configured through the Collaboration Brand Network Configuration (Co-BNC) framework demonstrate significant potential in augmenting organizational income and expanding Zakat, Infaq, and Shodaqoh (ZIS) fund collection. This study investigates the Co-BNC model within Muhammadiyah and Lazismu Charity organizations, examining its role in optimizing organizational performance and ZIS fundraising outcomes. A quantitative approach employing Structural Equation Modeling and path analysis was adopted. Data were collected from AUM and Lazismu management personnel comprising 42 respondents, analyzed using WarpPLS 7. Findings demonstrate that Co-BNC significantly enhances ZIS collection through the mediating roles of brand awareness and organizational income performance. ZIS serves as the terminal proxy reflecting revenue generated from Co-BNC-based brand awareness formation between AUM and Lazismu. Optimally configured Co-BNC strengthens mutual brand reinforcement, elevates AUM profitability, expands zakat nisab thresholds, and enables cost-efficient network collaboration across Muhammadiyah institutions, collectively maximizing ZIS fundraising performance.